Composition operators and closures of some Möbius invariant spaces in the Bloch space - Aulaskari, Rauno; Zhao, Ruhan (MATHEMATICA SCANDINAVICA, 2010)
Boundedness and compactness of composition operators between the Bloch space and the closure of some Möbius invariant subspaces in the Bloch space are characterized.